2005
DOI: 10.4049/jimmunol.174.2.619
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral “CD8 Tuning” Dynamically Modulates the Size and Responsiveness of an Antigen-Specific T Cell Pool In Vivo

Abstract: In this study, we suggest that CD8 levels on T cells are not static, but can change and, as a result, modulate CD8+ T cell responses. We describe three models of CD8 modulation using novel weak-agonist (K1A) and super-agonist (C2A) altered peptide ligands of the HY smcy peptide. First, we used peripheral nonresponsive CD8low T cells produced after peripheral HY-Db MHC class I tetramer stimulation of female HY TCR transgenic and wild-type mice. Second, we used genetically lowered CD8int T cells from heterozygot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
100
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 55 publications
6
100
0
Order By: Relevance
“…3a). Neither CD8 + T cells from untreated nor lower avidity K1A-D b -treated mice were able to suppress naive CD8 + T cell responses in vitro, confirming our previous results that a minimum avidity threshold is required for generation of CD8 lo T cells [17], and suggesting this is also the case for generation of suppressive ability.To confirm that the regulatory function lies within the CD8 lo T cell population, we further sorted purified CD8 + T cells into CD8 hi and CD8 lo T cells from tetramertreated mice. Following irradiation, only the CD8 lo T cells from HY-D b treated groups suppressed the response Figure 2.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…3a). Neither CD8 + T cells from untreated nor lower avidity K1A-D b -treated mice were able to suppress naive CD8 + T cell responses in vitro, confirming our previous results that a minimum avidity threshold is required for generation of CD8 lo T cells [17], and suggesting this is also the case for generation of suppressive ability.To confirm that the regulatory function lies within the CD8 lo T cell population, we further sorted purified CD8 + T cells into CD8 hi and CD8 lo T cells from tetramertreated mice. Following irradiation, only the CD8 lo T cells from HY-D b treated groups suppressed the response Figure 2.…”
supporting
confidence: 87%
“…We argue that these observations are CD8 + examples of the peripheral dynamic T cell "avidity regulation" model, in which T cell clones with certain avidity for cognate antigen are selectively suppressed [17,21,22], in this case by stable down-regulation of CD8 expression, which greatly impacts the ability of the CD8 + T cell to respond to low avidity antigens [17]. Here we describe that such CD8 lo T cells, despite being significantly nonresponsive to antigen per se [17][18][19][20] can also mediate dose-dependent suppression of naive, but not memory, CD8 + T cell proliferation to HY antigen in vitro. When adoptively transferred to naive female B6 recipients, HYspecific CD8 lo T cells prolong male skin graft survival in vivo.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Previous findings from the same group have demonstrated that HY-specific TCR transgenic cells with low CD8 expression levels respond with low avidity to cells presenting male antigens [24]. Consequently, the authors speculate that the CD8 low Treg that are induced after immunization with HY tetramers respond less well to normal levels of MHC class I/peptide on grafted male cells and that this feature provides, somehow, an explanation for their regulatory properties.…”
mentioning
confidence: 90%
“…One possible explanation could be the different balance between activating and inhibitory influences in the two situations. In memory T cells, the threshold for stimulation is much lower than in naive T cells [24], which means that memory T cells will be more prone to execute their effector functions at lower levels of stimulation. In such a situation, the immunoregulatory molecules derived from Treg will perhaps not be present in quantitatively large enough numbers to counteract the triggering pathways.…”
mentioning
confidence: 99%